Conceptualising historical legacies for transitional justice history education in postcolonial societies. Issue 1 (31st October 2022) - Robinson, Natasha
Abstract : Addressing legacies of past injustice is a central concern for transitional justice. It has most commonly been attempted through a 'truth-telling' approach; it is assumed that if the truth of past injustices is made known, then justice can be acted upon within contemporary society. 'Truth telling' – and disciplinary approaches to learning about past injustices – is therefore a central rationale for postconflict history education. However, this article argues that 'truth telling' is not sufficient for transitional justice history education. Instead, greater attention should be paid to historical legacies, since it is beliefs about how the past impacts the present that shape reparation decision making. While the concept of historical legacies has been under-theorised by transitional justice scholars, this article demonstrates how recent work from the field of history education can be helpful. In particular, this article distinguishes between legacies as essentialised causal relationship between the past and the present, and legacies which refer to how people construct causal relationships between the past and present. By understanding legacies as constructs, this article encourages history educators to engage with how identity factors may mediate the way in which students understand the impact of the past on the present, particularly in postconflict societies.